COHESIVE FUZZY GRAPHS WITH APPLICATION IN URBAN DEVELOPMENT AND INFRASTRUCTURE COLLABORATION - S. Sheelarani; J. Jon Arockiaraj (Journal of Mechanics of Continua and Mathematical Sciences, 2024)
Public officials face challenges when illustrating and assessing strategies for developing active communities, necessitating a thorough examination of interministerial collaboration. This research is focused on introducing a Cohesive fuzzy graph that portrays cooperation and contributing factors between various ministries. The current graph can adeptly convert complex information by utilising two variables, thereby enhancing the fidelity and effectiveness of hesitant fuzzy graphs in representing both information and phases. We demonstrate a cohesive fuzzy graph's practical application using the ideas of score function and deviation degree.